Adoption, returns and variation of information and communication technology in Sub-Sahara Africa - Agyire-Tettey, Frank (2015)
Increased competition in the modern economy has driven firms to search for increased efficiency, as well as an increased access to information. This, in conjunction with the continual advancement in information and communication technologies (ICTs), and coupled with falling prices, has inspired firms to adopt different types of ICTs in order to be competitive. This has heightened and provoked research interest in the effectiveness of ICT at the firm level. However, most studies on the use and effectiveness of ICTs in firm development have focused on developed economies, with mainly anecdotal evidence on many developing countries.